2020
DOI: 10.7150/ijms.49574
|View full text |Cite
|
Sign up to set email alerts
|

Modified three-level techniques of retroperitoneal laparoscopic procedures to treat adrenal lesions for patients with BMI ≥ 25 Kg/m2

Abstract: Objective: To evaluate the modified Zhang's 'three-level' technique of retroperitoneal laparoscopic adrenalectomy (RLA) to treat adrenal lesions for patients with BMI of 25-30 Kg/m 2 . Methods: A retrospective analysis was performed in all patients with BMI of 25-30 Kg/m 2 in our hospital from January 2014 to December 2019. Those who underwent laparoscopic adrenal surgery were divided into two groups on the basis of the technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The surgical procedures have been described in a previous report. [12] We con rm that all methods were performed in accordance with the relevant guidelines and regulations. This study was approved by the Ethics Committee of Fujian Provincial Hospital, Fujian Province, People's Republic of China (approval K2023-05-008).…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The surgical procedures have been described in a previous report. [12] We con rm that all methods were performed in accordance with the relevant guidelines and regulations. This study was approved by the Ethics Committee of Fujian Provincial Hospital, Fujian Province, People's Republic of China (approval K2023-05-008).…”
Section: Methodsmentioning
confidence: 85%
“…[11] Compared to modi ed three-layered retroperitoneal laparoscopic adrenalectomy (MTRLA), unexpected TA rates were signi cantly higher in patients with high body mass index (BMI). [12] And higher BMI indicates a higher mayo adhesive probability (MAP) score. [13] A higher MAP score was associated with the operative time in LA [14,15] , as well as estimated blood loss and drainage tube removal time.…”
mentioning
confidence: 99%
“…A limitation of this study is that it was a retrospective study conducted at our institution. Although previous studies have shown the advantages of the MT procedure ( 16 ), other surgeons with comparable experience may perceive the difference to be insignificant because of the significant differences in sample sizes between the two groups. Stratified analyses for patients with different MAP scores have not been conducted at this time ( 14 ) and adrenal lesion locations, which is our next step.…”
Section: Discussionmentioning
confidence: 92%
“…The detailed steps have been described in the previous article ( 16 ).The surgical video still was demonstrated in Figure 2 , and the complete procedure video ( 17 ) can be accessed by scanning Figure 2D . The schematic diagram of modified and three-level technique of retroperitoneal laparoscopic adrenalectomy was shown on Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation